Relationship between knowledge and adherence of type 2 diabetes mellitus patients in treatment: A cross-sectional study - Akbar, M Agung; Harto, Toto; Al Hakim, Abdul Rahman (Indonesian Journal of Health Services, 2024)
Background: Type 2 diabetes mellitus is a chronic metabolic disorder that requires long-term pharmacological treatment and sustained adherence to therapy to achieve optimal glycemic control and prevent complications. However, many patients experience difficulties maintaining consistent treatment adherence, which may worsen disease outcomes. Patient knowledge regarding diabetes management is considered an important factor influencing adherence behavior. Understanding the relationship between knowledge and treatment adherence is therefore essential for improving diabetes management strategies in primary healthcare settings. Objective: This study aimed to analyze the relationship between knowledge and treatment adherence among patients with type 2 diabetes mellitus in a primary healthcare setting. Methods: This study employed a quantitative descriptive design with a cross-sectional approach. The research was conducted in October 2022 in the working area of UPTD Puskesmas Tanjung Baru. The study population consisted of patients diagnosed with type 2 diabetes mellitus, and a total of 30 respondents were included using a total sampling technique. The independent variable was patient knowledge regarding diabetes mellitus, while the dependent variable was treatment adherence. Data were collected using structured questionnaires and adherence checklists. Descriptive statistics were used to summarize respondent characteristics, and bivariate analysis was performed using the Chi-square test with a significance level of α = 0.05. Statistical analysis was conducted using SPSS software. Results: The results showed that most respondents had a moderate level of knowledge (43.3%), followed by good knowledge (33.3%) and poor knowledge (23.3%). Regarding treatment adherence, the majority of respondents demonstrated moderate adherence (53.3%), while 26.7% were categorized as adherent and 20.0% were non-adherent. The Chi-square test indicated a statistically significant relationship between knowledge and treatment adherence among patients with type 2 diabetes mellitus (p = 0.011). Respondents with higher knowledge levels tended to demonstrate better adherence to diabetes treatment. Conclusion: Knowledge level is significantly associated with treatment adherence among patients with type 2 diabetes mellitus. Improving patient knowledge through targeted education and counseling programs may enhance treatment adherence and support better diabetes management outcomes in primary healthcare settings.